Alexey Remizov: between Reception and Self-Reflection (The Chosen Pages of the Scrapbook “Foreign Censorship” 1923–1931) - Elena R. Obatnina (Studia Litterarum)
The subject of this study is relationship of Alexey Remizov with his readers from the professional literary community that draws from the materials of the author’s scrapbook Foreign Censorship — unknown artifact created in 1923–1931. The album as a product of the literary “everyday life” (“byt”) reflects the process of Remizov’s selfreflection prompted by various instances of editing and criticism of his works in the emigrant press. The author of this article explains the meaning that Remizov associated with censorship under the conditions of emigration and highlights the hidden plots of Remizov’s biography connected with the publication of his censored works. The collection of materials in the scrapbook reveals Remizov’s rejection of the ready patterns of the literary norm and stereotypes that affected the perception of his work by editors. Analysis of the scrapbook’s documents has allowed disclose the reasons for imposing editorial restrictions on Remizov. The author specifically focuses on the critical reviews selected by Remizov for his scrapbooks demonstrating the discrepancy between Remizov’s own “horizon of expectation” and that of his critics. The article is followed by the publication of the hitherto unpublished archival materials, a welcome addition to Remizov’s biography that reveals his place in the Russian émigré literary scene.